2019
DOI: 10.1172/jci123540
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-intrinsic PIK3CA represses tumor immunogenicity in a model of pancreatic cancer

Abstract: The presence of tumor-infiltrating T cells is associated with favorable patient outcomes, yet most pancreatic cancers are immunologically silent and resistant to currently available immunotherapies. Here we show using a syngeneic orthotopic implantation model of pancreatic cancer that Pik3ca regulates tumor immunogenicity. Genetic silencing of Pik3ca in Kras G12D /Trp53 R172H -driven pancreatic tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 66 publications
5
58
0
Order By: Relevance
“…We also demonstrate that tumor tumor-intrinsic factors such as SMAD4 act as a barrier against tumor immune escape. As reported, growth of KRAS mutant pancreatic cancer cells with targeted inactivation of PIK3CA, a parallel branch of the KRAS signaling pathway, is also inhibited in syngeneic wild-type mice but not in nude mice due to the upregulation of MHC class I expression 58 . The results imply that the ability of mutant KRAS to modulate tumor immunity (via involvement of the RAF, PI3K, and MYC pathways) is an essential component of its oncogenicity, and that treatment of cancer will be improved by different modalities acting to simultaneously inhibit KRAS and activate immune pathways suppressed by cancer.…”
Section: Discussionmentioning
confidence: 56%
“…We also demonstrate that tumor tumor-intrinsic factors such as SMAD4 act as a barrier against tumor immune escape. As reported, growth of KRAS mutant pancreatic cancer cells with targeted inactivation of PIK3CA, a parallel branch of the KRAS signaling pathway, is also inhibited in syngeneic wild-type mice but not in nude mice due to the upregulation of MHC class I expression 58 . The results imply that the ability of mutant KRAS to modulate tumor immunity (via involvement of the RAF, PI3K, and MYC pathways) is an essential component of its oncogenicity, and that treatment of cancer will be improved by different modalities acting to simultaneously inhibit KRAS and activate immune pathways suppressed by cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Phosophoinosotiol‐3‐kinase (PI3K) is a downstream effector of KRAS. The kinase, PI3KCA, has been implicated in driving reduced MHC class I and CD80 expression in pancreatic cancer cells resulting in impaired T cell recognition of tumor cells 33 . Understanding the tumor cell‐intrinsic properties of pancreatic cancer that drive immune evasion may lead to novel combination treatment approaches to increase the effectiveness of immunotherapy.…”
Section: Immune Landscape Of Pancreatic Cancermentioning
confidence: 99%
“…Cancer cells have the ability to reshape the surrounding microenvironment for their survival, growth, invasion, and immune escape (Quail and Joyce, 2013;Spranger and Gajewski, 2018). Our study and those by others have demonstrated that PTEN loss or PI3K-AKT pathway activation promote an immunosuppressive microenvironment, resulting in silenced immune response, decreased tumor antigen presentation and decreased CD8 + T cell infiltration, which lead to resistance to ICT (Chandrasekaran et al, 2019;Garcia et al, 2014;George et al, 2017;Peng et al, 2016;Sivaram et al, 2019;Wu et al, 2019). We found in this study that PI3K inhibition by BAY1082439 not only inhibits PTEN null prostate cancer cell growth, but also promotes anti-tumor immunity via increased IFNα and IFNγ pathway activities, upregulated expression and secretion of crucial CD8 + T cell attracting cytokines and increased antigen presentation (Fig.1).…”
Section: Discussionmentioning
confidence: 53%
“…However, targeting PI3K pathway is not a simple task, especially to achieve synergy with ICT, as PI3K pathway plays significant roles on both sides of the aisle. As one of the most important oncogenic pathways, PI3K activation promotes cell proliferation, survival, migration, angiogenesis, metabolic reprograming as well as an immune suppressive environment (Cheng et al, 2020;Okkenhaug et al, 2016;Sivaram et al, 2019;Thorpe et al, 2015;Wu et al, 2019); on the other hand, PI3K is also a critical regulator for the functions of immune cells within the tumor microenvironment, and inhibition of PI3K activity in these immune cells may be detrimental for ICT (Carnevalli et al, 2018;De Henau et al, 2016;Kaneda et al, 2016;Lu et al, 2017). To make things even more complicated, there are four isoforms in the class I PI3K family:…”
Section: Introductionmentioning
confidence: 99%